Memandang Eksistensi Pasukan Merah Dayak dalam Terang Iman Katolik - Nyaming, Fransiskus Gregorius (Perspektif, 2024)
This research pays attention to the existence and activities of the Tariu Borneo Bangkule Rajakng Red Troop (TBBR). With its commitments: uniting the Dayak community, caring for nature, preserving Dayak customs and culture, defending and fighting for the dignity of fellow Dayak people who are often oppressed by injustice, it has become a special attraction for young Dayak people to join. These commitments certainly deserve high appreciation. However, it is deemed necessary to conduct a study from the perspective of the Catholic faith on their existence and activities. The basic reason is based on empirical facts, namely that Pangalangok Jilah, the Commander in Chief, and most of the troop members embraced Catholicism. Therefore, this research believes that the solidarity and compassion of the TBBR Red Troop must also be based on Christian values and teachings. Through literature studies, especially Magisterium teachings and Church documents as well as several supporting sources, this research does not focus only on providing critical input and note. Since what the TBBR Red Troop is committed to is also part of the Church's commitment, this research also offers what kind of attitude the local Church should take when dealing with this particular community.